Cost-consequence analysis of the enhanced recovery after surgery protocol in major lung resection with minimally invasive technique (VATS) - Buja, Alessandra; De Luca, Giuseppe; Dal Moro, Stefano; Mammana, Marco; Zanovello, Anna; Miola, Stefano; Boemo, Deris Gianni; Storti, Ilaria; Bovo, Pietro; Zorzetto, Fabio; Schiavon, Marco; Rea, Federico (Frontiers in Surgery, 2024)
BackgroundERAS is an evidence-based multimodal perioperative protocol focused on stress reduction and promoting a return to function. The aim of this work is to perform a cost-consequence analysis for the implementation of ERAS in major lung resection by means of minimally invasive surgery (VATS) from the public health service perspective, evaluating resource consumption and clinical outcomes with respect to a control group of past patients, which did not adopt an ERAS protocol.MethodsOutcome differences (re-intervention rates, major and minor intraoperative and postoperative complications, readmissions, and mortality) as well as the costs of preoperative, operative, and postoperative care were estimated. The sample consisted of 64 consecutive patients enrolled in the ERAS programme between April 2021 and August 2022, compared to a control group (historical cohort) comprising 31 patients treated from April 2020 to December 2020, prior to the implementation of the ERAS programme. The study sample comprises patients who fulfil the established ERAS protocol inclusion criteria, including general criteria (acceptance of the protocol, proximity of residence, absence of contraindications to physiotherapy and early mobilisation), surgical criteria (anatomical lung resection up to lobectomy, absence of extensive resection, good possibility of conducting the operation in VATS) and anaesthesiologic criteria (ASA ≤2). Costs were quantified using the national health system perspective.ResultsThe average length-of-stay was at least one day shorter in the ERAS group [<0.001. Average total costs including entire pathway healthcare costs were substantially reduced for ERAS-VATS patients (mean: € 5,955.71 vs. €6,529.41 Δ = −573.70 p = 0.018)]. Specifically, the median costs of the admission phase were significantly different between the two groups (median: €4,648.82 vs. €5,596.58, p = 0.008), with a reduction in hospital stay expenditure in the ERAS-VATS group (median: €1,599.62 vs. €2,399.43, p = 0.025). No significant differences were found regarding major clinical outcomes.ConclusionsThe implementation of an ERAS programme is a dominant strategy, representing an intervention capable of reducing overall costs in the context of elective anatomical lung resection with VATS without any significant differences in major complications and re-intervention rates.